Remineralizing effect of Xilitol, Juniperus Communis and Camellia Sinensis added to a toothpaste : an in vitro study = Efecto remineralizante del Xilitol, Juniperus Communis y Camellia Sinensis adicionados en pastas dentales : estudio in vitro - Jiménez Gayosso, Sandra I.
The aim of this study was to explore the remineralizing effect of toothpastes based on Xilitol, Camellia Sinensis and Juniperus Communis. An in vitro experimental study was carried out in an 18 human premolars sample, which were treated with one of the 3 evaluated toothpastes and a control fluoride one. The atomic percentages of Ca and P were evaluated by Energy Dispersive X-ray Spectroscopy (EDS). In addition, the enamel surface of treated teeth was visualized by Scanning Electron Microscopy (SEM). The evaluations were carried out in three stages: pre-treatment, after an artificial demineralization process and after the treatment with the toothpastes. In the statistical analysis, the one-way ANOVA and Pearson correlation tests were used. Xilitol and Juniperus Communis showed the greatest gain of P ions compared to the control group (p<0.01). As for Ca, the group treated with xylitol-based toothpaste showed more ion gain compared with the control group (p<0.01). In the Pearson correlation test between Ca and P, statistically significant correlations were observed in all groups (p<0.01), ranging between r=0.7413 (Xylitol Group) and r=0.9510 (Control Group). We concluded that Xylitol paste showed the highest remineralizing property, both in the EDS analysis and in the SEM images.